Integrated solar panel with automatic cooling system - Bachik, Muhammad Syamil (2022)
Sun's nuclear fusion process creates solar energy. Malaysia, a tropical country, has sun radiation and natural light that may illuminate building interiors year-round. New technology can make advantage of these bountiful resources. "Green" technology doesn't emit greenhouse gases. Solar energy has been used to create electricity and heat for ages. Solar energy may cut greenhouse gas emissions, the research found. Greenhouse gas emissions harm our environment by trapping heat and accelerating climate change. Integrated solar panels, solar panel roof tiles, solar control glass, and rooftop solar trackers may be utilised to reduce this effect. During this research, a number of hurdles and problems have emerged that must be solved to increase solar panels' power-producing potential. This concept for an innovation idea has multiple purposes, the first of which is to identify the current solar technology that is being utilised in developed nations. The second goal is to suggest the enhanced solar technology that would replace the present solar technology. and ultimately, to evaluate the commercial viability of the solar technology that is being suggested. The approach for the creation of the connected subject about the innovation concept of solar panel from the literature review and simulation that will be done using Sketch Up, Key Animation, and Cap Cut to accomplish the goals of the research study. According to the results of the research, the innovative concept offers a more effective way to produce power with the current cooling system, and it also has the potential to be more aesthetically pleasing. As findings, it is thought that this innovation concept would be able to have a beneficial influence, and it may have potential in terms of its marketability as one of the construction parts that is a window in Malaysia.